Annual world Bank Conference on development Economics 1998 : [proceedings] - World Bank Annual Conference on development Economics Washington, DC 1998; Stiglitz, Joseph E.; Pleskovic, Boris (Washington,D.C World Bank, 1999)
he 1998 Annual World Bank Conference on Development Economics, the tenth anniversary, was held at the Bank on April 20-21, 1998. The discussions focused on four areas of inquiry: 1) the role of geography in countries ' success, 2) the role of effective competition and regulatory policies, 3) the causes of financial crises and ways to prevent them, and 4) the effects of ethnic diversity on democracy and growth. The welcoming address by World Bank President James D. Wolfensohn, the opening remarks by chief Economist Joseph Stiglitz, and the tenth anniversary address by the International Monetary Fund Deputy Managing Director Stanley Fischer all focused both on the role of the conference and on the changing perspectives for development.
Introduction / Boris Pleskovic and Joseph E. Stiglitz -- Is geography destiny?: The Role of geography in development / Paul Krugman -- Gepgraphy and economic development / John luke Gallup and Jeffrey D. Sachs with Andrew D. Mellinger -- Competition and regulation policy in developing countries: Regulatory priorities for infrastructure sector reform in developing countries / Paul L. joskow -- Competition, information and development / Jean-Jacques Laffont -- Financial market liberalization in developing countries: theory and practice: International adjustment in the face of imperfect financial markets / Bruce Greenwald -- Financial liberalization and financial fragility / Asli Demirguc-Kunt and Enrica Detragiache -- Ethic conflicts: Structure and strategy in ethic conflicts: A few steps toward synthesis / Donald L. Horowitz -- The political economy of ethnicity / Paul Collier
Includes bibligraphies
Keywords: Economic development; ECONOMIC DEVELOPMENT; DEVELOPMENT POLICY; COMPETITION POLICY; ECONOMIC RESEARCH; FINANCIAL MARKET; DEVELOPING COUNTRIES; CONFERENCES